KEDUDUKAN EFEK DALAM HAL PENJUAL DINYATAKAN PAILIT PADA TRANSAKSI SHORT-SELLING DI PASAR MODAL - Rahmadiani Putri Nilasari (Universitas Airlangga, 2013)
Basically, short selling transaction is the practice of selling stock without having first. Short selling is divided into two types of naked shor selling and covered short selling. In naked short selling, securities transactions without assurance from the lender. The practice of naked short selling is banned because it is damaging the market. Whereas the covered short selling is selling transaction that must have a guarantee. Covered short selling is the practice of selling securities that is allowed in Indonesia and supported by Bapepam-LK with provide lending and borrowing facilities by PT. KPEI. In the lending and borrowing securities mechanism, when the securities is on the borrower or another party, the lender still entitled to receive the rights in this securities. It shows that the transfer of ownership of securities on loan is not happen in full. Moreover there is recall mechanism that lenders can recall the loan any time before maturity date.